Improving English Learning Outcomes with Learning Interests, Learning Motivation, through Learning Activities Learners in the Covid-19 pandemic - Rindika Pramadanti (Formosa Journal of Multidisciplinary Research, 2022)
This research aims to find out the influence of English learning outcomes on interests and learning Motivation through learning activities of learners during the Covid-19 pandemic. With a population of class XI of 320 people. The sample took using the Cluster sampling method for as many as 172 learners with morgan's table as a reference to the number of research samples beyond the number of pieces for the validity and reliability test for as many as 32 students. Path analysis uses multiple linear regressions with two substructures. Our F test reveals the simultaneous influence of independent variables on dependent variables. The t-test test tests each variable independently of the dependent variable partially among direct or indirect effects. This research yielded several conclusions, both free variables, interest in learning, and learning. Motivation affects the bound variables, namely teaching activities, learning outcomes, and learning interests.